Client Relationship Marketing Practices: An Exploratory Study of the Legal Industry - Kok Ming Woo (2018)
© 2014, Copyright © Taylor & Francis Group, LLC. This article aims to identify and examine the responsibilities of the marketing specialists and legal practitioners in the legal industry at different stages of the client relationship development process. A conceptual framework is proposed to analyse the single case study of this research. The relationship marketing practices of a global law firm were examined through fifteen in-depth semi-structured interviews with key personnel. Ten client relationship marketing practices were identified. Whereas organising and attending social events, managing the communications or interactions process, managing the cross-selling, service recovery, changing the impression, truly understanding clients' businesses and industries and other small little gestures are similar to the findings of Claycomb and Martin (2002), social bonds beyond the professional level, treating every job seriously regardless of the size, and utilising client relationship management software were three practices that emerged from this study. Although the ten practices presented are pivotal in contributing to a successful client relationship, further research is needed to examine the effects of each practice and the quality of the client relationship. This article demonstrates that in order to succeed in the highly competitive marketplace, law firms need to understand not only the potential outcomes of each relationship marketing practice but also how to practice it systematically. A new relationship development process model incorporating the essence of the customer relationship life cycle was developed and its practicality was confirmed by the research findings.